Hubungan Keragaman Media Sosial dengan Perilaku Fear of Missing out (FoMO) pada Remaja: Kelas XI di SMAN 4 Tuban - Alya Marsasetya Fahman; Mokhamad Nurhadi; Tiara Putri Ryandini; Mei Widyawati (Inovasi Kesehatan Global, 2026)
The diversity of social media used by teenagers today can influence Fear of Missing Out (FoMO) behavior, a condition where someone feels left out of information, trends, or activities carried out by others. This condition is characterized by fear, anxiety, difficulty controlling the desire to stay connected, and a tendency to compare oneself with others on social media. Teenagers are the group most vulnerable to FoMO due to their high intensity of social media use and their still-developing social needs. This reseach seeks to examine the association between scial media diversity and FoMO behavior among eleventh-grade student at SMAN 4 Tuban. The study employed a quantitative analytic design using a cross-sectional approach. The research population consists of all 11th grade students, totaling 157 respondents, selected using simple random sampling. The instruments used are a social media diversity questionnaire and a FoMO behavior questionnaire. Data analysis uses the Chi-Square test with a significance level of α = 0.05. The results of the study show a p-value of 0.000, which means p < 0.05, so H1 is accepted. This shows that there is a significant relationship between social media diversity and FoMO behavior in adolescents. The more diverse the social media platforms used, the higher the tendency for adolescents to experience FoMO. Based on these results, it can be concluded that social media diversity influences FoMO behavior among 11th grade students at SMAN 4 Tuban.